Polycarbonate type polythionocarbamate meniscus substitute and preparation method thereof
Polycarbonate polysulfurethane materials were prepared through molecular design and combined with polyamide-based fiber fabrics. Through cross-linking and click reaction of zwitterionic salts, the problems of poor mechanical properties and contusion of cartilage were solved, and meniscus substitutes with high mechanical properties, low wear and excellent biocompatible meniscus substitutes were achieved.
Patent Information
- Application Number
- CN202411630335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-25
AI Technical Summary
Existing polycarbonate polyurethane meniscus replacements have problems with poor mechanical properties and contusion of cartilage.
Polycarbonate polysulfurethane materials are prepared through molecular design and combined with polyamide-based fiber fabrics to improve the mechanical properties and biocompatibility of the materials through cross-linking and click reaction of zwitterionic salts.
A polycarbonate polythiourethane meniscal substitute with high mechanical properties and low wear is achieved, which reduces damage to cartilage and promotes the regeneration and differentiation of chondrocytes.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a polycarbonate type polythiourethane meniscus substitute and a preparation method thereof. The invention belongs to the field of biocomposite materials. Background Art
[0002] The meniscus is a pair of semilunar fibrocartilage located between the femoral condyle and the tibial plateau, which plays an important role in stabilizing the knee joint, transmitting load, absorbing shock and lubricating the joint. When the meniscus is bruised, the normal function of the knee joint will be greatly reduced, the knee joint will be severely burdened, especially during strenuous physical activities, and the meniscus cannot be regenerated. Meniscus reconstruction is one of the commonly used methods for clinical treatment of meniscus injuries, among which artificial meniscus has become a research and development hotspot because of its non-immunogenicity, sufficient source and low price.
[0003] The ideal meniscus substitute should have similar geometric features to the natural meniscus, anisotropic mechanical properties, excellent biocompatibility and long-term stability in vivo. To this end, researchers have developed various types of meniscus substitutes, including polytetrafluoroethylene, polyester, porous polyurethane, polyvinyl alcohol hydrogel, polycarbonate polyurethane, etc. However, the above meniscus substitutes all have some shortcomings, such as: polytetrafluoroethylene materials have low strength and poor wear resistance, and are prone to deformation and wear after implantation, resulting in the deposition of fragments in the joint cavity and the formation of synovitis, damaging the articular cartilage; polyester also has synovitis and articular cartilage wear; porous polyurethane also has the problem of damaging the articular cartilage; polyvinyl alcohol hydrogel has poor mechanical properties; polycarbonate polyurethane has a large friction coefficient and damages the cartilage tissue, etc.
[0004] Therefore, considering the above-mentioned scientific research status and the urgent need for polycarbonate polyurethane meniscus substitutes, it is of great significance to develop a polycarbonate polyurethane meniscus substitute material with high mechanical properties, low wear and high biocompatibility. Summary of the invention
[0005] The purpose of the present invention is to provide a polycarbonate type polythiourethane meniscus substitute and a preparation method thereof in view of the problems of poor mechanical properties and cartilage contusion in the prior art artificial meniscus substitutes. The present invention prepares polycarbonate type polythiourethane meniscus substitute materials and polyamide-based fiber fabrics by molecular design and prepares them by structural optimization design. The technical solution adopted by the present invention to solve its technical problems is: The present invention provides a method for preparing a polycarbonate-type polythiourethane, comprising the following steps: S11, conducting an ester exchange reaction between a diol and dimethyl carbonate to obtain an intermediate product 1I; S12, subjecting the intermediate product 1I to a ring-opening-cyclization reaction with epichlorohydrin to obtain an intermediate product 1II; S13, subjecting the intermediate product 1II to a ring-opening-cyclization reaction with carbon disulfide to obtain an intermediate product 1III; and S14, subjecting the intermediate product 1III to a ring-opening reaction with a diamine to obtain a target product, namely, a polycarbonate-type polythiourethane.
[0006] Furthermore, the molar ratio of the diol to dimethyl carbonate is 1.5-2.5:1.
[0007] Furthermore, the molar ratio of the intermediate product 1I to epichlorohydrin is 1:2.
[0008] Furthermore, the molar ratio of the intermediate product III to carbon disulfide is 1:2.
[0009] Further, the molar ratio of the intermediate product 1III to the diamine is 1:1; and The diamine is a macromolecular diamine and a small molecular diamine added in a molar ratio of 2.5-3.5:6.5-7.5.
[0010] Further, the macromolecular diamine is polyethylene glycol diamine and / or polyether diamine; and The small molecule diamine is a mixture of aliphatic diamine and aromatic diamine.
[0011] The present invention also provides a polycarbonate-type polythiourethane, which is prepared by the above-mentioned preparation method.
[0012] Another object of the present invention is to provide a method for preparing a polyamide-based fiber fabric, comprising the following steps: S21, condensing a dibasic acid and a polyamine to obtain an intermediate product 2I; S22, subjecting the intermediate product 1I to a ring-opening reaction with the intermediate product 2I to obtain the intermediate product 2II; S23, spinning and combing the intermediate product 2II to obtain a polyamide-based fiber fabric.
[0013] Furthermore, the molar ratio of the dibasic acid to the polyamine is 0.5-1.0:1.0; and, The dibasic acid is an aromatic diacid; The polyamine is a diamine and a triamine added in a molar ratio of 0.80-0.95:0.05-0.20; The diamine is a water-soluble diamine; including polyether diamine; The triamine includes melamine.
[0014] Furthermore, the intermediate product 2I and the intermediate product 2II are added in a molar ratio of 1.0:1.0.
[0015] The present invention also provides a polyamide-based fiber fabric prepared by the above-mentioned preparation method.
[0016] Another object of the present invention is to provide a method for preparing a polycarbonate-type polythiourethane meniscus substitute, comprising: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it, and curing it to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
[0017] Further, the zwitterionic salt contains a carbon-carbon double bond structure; and, The zwitterionic salt contains bromide ions.
[0018] The present invention also provides a polycarbonate-type polythiourethane meniscus substitute, which is prepared by the above-mentioned preparation method.
[0019] Beneficial effects of the present invention: (1) The present invention provides a polycarbonate-type polythiourethane meniscus substitute, the internal matrix material of which is a polycarbonate-type polythiourethane material. First, polythiourethane has the flexibility of polyurethane and the durability of polysulfide rubber, and has better mechanical properties; second, the polycarbonate-type structure has a higher modulus, which further improves the mechanical properties; third, the large number of thiol structures generated by the reaction not only retain the reaction activity, but also have excellent biocompatibility; fourth, the molecular functionalization design is carried out on the amine source, and the use of large molecular water-soluble high molecular weight diamine and small molecular diamine compound can effectively improve the hydrophilicity and mechanical properties of the matrix.
[0020] (2) The present invention provides a polycarbonate-type polythiourethane meniscus substitute, wherein the outer polyamide-based fiber fabric is a block copolymer structure of a polythiourethane structure and a polyamide structure. First, polyamide fiber (especially aramid) has excellent mechanical properties and chemical corrosion resistance, which can effectively ensure the dimensional retention of the material in a complex environment; second, the polythiourethane structure has similar compatibility with the internal matrix material, reducing relative slip during stress deformation; third, the water-soluble polyamine structure gives the fiber fabric excellent hydrophilicity, effectively improving the lubrication performance between the meniscus substitute and the cartilage tissue, reducing wear and less contusion.
[0021] (3) The present invention provides a method for preparing a polycarbonate-type polythiourethane meniscus substitute, which is prepared by placing an internal matrix material and an external fiber fabric in a mold and cross-linking them with a zwitterionic salt. First, the carbon-carbon double bond structure in the zwitterionic salt can undergo a "thiol-ene" click reaction with the thiol groups in the matrix material and the external fiber fabric, thereby improving the mechanical properties of the matrix and effectively reducing the relative slip between the matrix material and the fiber fabric, further improving the mechanical properties; second, the bromide ions in the zwitterionic salt have the function of inducing chondrocyte regeneration and differentiation, and can effectively promote cartilage repair; and the bromide ions form an ammonium salt structure with the ammonium ion, which has a sustained release and long-lasting effect.
[0022] (4) The present invention provides a method for preparing a polycarbonate-type polythiourethane meniscus substitute, which has mild reaction conditions, simple operation steps, high feasibility, and is suitable for large-scale production. DETAILED DESCRIPTION
[0023] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0024] The purpose of the present invention is to develop a polycarbonate-type polythiourethane meniscus substitute to solve the problems of poor mechanical properties and cartilage bruising in existing polycarbonate-type polythiourethane meniscus substitutes.
[0025] The idea is to achieve this by taking the main physical properties of the natural meniscus (tensile strength 13.25MPa, friction coefficient 0.14, relative cell survival rate 100%) as the target, and using polycarbonate polyurethane as the main material, through chemical modification and physical structure design, to improve the mechanical properties of the material and the problem of cartilage contusion. First, the overall structure is designed, with modified polycarbonate polyurethane (i.e. polycarbonate polythiourethane) as the matrix material; and a "mesh cover" is designed for this matrix material, and then the matrix material and the "mesh cover" are formed into a whole to solve the problem of insufficient mechanical properties; at the same time, the matrix material and the "mesh cover" are chemically modified to solve the problem of poor mechanical properties and cartilage contusion; in addition, for cartilage contusion, on the one hand, the friction coefficient is reduced; on the other hand, it is solved by promoting cartilage proliferation compensation.
[0026] For chemical modification, the matrix is specifically: polycarbonate polythiourethane is used as the main matrix, and the molecular structure is designed to give the structural properties of polycarbonate, polyurethane, and polysulfide rubber; at the same time, the selection of amine sources is designed to improve its hydrophilicity, which is beneficial to biocompatibility; and the thiol structure for further reaction is retained; the external "mesh cover" is specifically: prepared by copolymerization of polyamide and polythiourethane, which not only improves the compatibility with the matrix, effectively provides the mechanical strength of the fiber structure, and enhances the hydrophilicity; in addition, the zwitterionic salt (ion exchange with bromide salt to form new ions) solution can be used as a crosslinking agent, hydrophilic agent, and cell proliferation promoter. The two materials are "integrated" according to the structural design, that is, placed in a zwitterionic salt solution for crosslinking to form a whole.
[0027] The theoretical basis for the realization is: the polycarbonate polythiourethane material first undergoes an ester exchange reaction to prepare a diol containing a carbonate structure; then undergoes a ring-opening-elimination-cyclization reaction with epichlorohydrin; then undergoes a ring-expansion reaction with carbon disulfide; and finally undergoes a ring-opening reaction with an amine source. The polyamide-based fiber fabric ("mesh") is prepared by separately preparing a polyamide prepolymer (amino-terminated), and then undergoes a ring-opening reaction with cyclothionone to obtain the product. "Integration", the two materials are placed in a zwitterionic salt solution according to the structural design, taken out, dried, UV-cured, and subjected to a click reaction to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute. The embodiments of the present invention are as follows: The embodiment of the present invention provides a method for preparing a polycarbonate-type polythiourethane, comprising the following steps: S11, N2 protection, mix diol and dimethyl carbonate, add catalyst A, stir, heat to 160-180°C, react for 1-3h, and obtain intermediate 1I.
[0028] The molar ratio of the diol to dimethyl carbonate is 1.5-2.5:1.
[0029] The diol may be ethylene glycol, 1,2-propylene glycol, 1,4-butanediol, 1,5-pentanediol, etc.; and preferably 1,4-butanediol; The amount of the catalyst A is 0.05-0.2wt% of the total mass of the reactants; The catalyst A may be titanium glycolate, tetrabutyl titanate, tetraisopropyl titanate, etc., and tetrabutyl titanate is preferred.
[0030] S12, the intermediate product 1I, epichlorohydrin and BF3 ether are mixed, heated to 40-80°C, and reacted for 2-8h; allowed to stand, and distilled under reduced pressure at 40°C to obtain a concentrate; sodium hydroxide solution is added, stirred at 40-80°C for 0.5-5h, and concentrated by distillation under reduced pressure, and washed with deionized water A 3 times to obtain the intermediate product 1II; The usage ratio of the intermediate product 1I, epichlorohydrin, sodium hydroxide, and deionized water A is 1 mol: 2 mol: 2 mol: 500 mL; The amount of BF3 ether used is 2.0-3.0wt% of the total mass of the reactants; The concentration of the sodium hydroxide solution is 30wt%.
[0031] S13, add the intermediate product 1II, carbon disulfide and catalyst B to tetrahydrofuran, place in an ice bath, stir for 2-4 hours, remove the ice bath, and continue stirring at room temperature for 18-24 hours; after the reaction is completed, distill under reduced pressure, add deionized water B, and shake; add chloroform to extract, separate the liquids, take the oil phase, add anhydrous sodium sulfate to dry, filter, take the filtrate, distill under reduced pressure, and dry in a vacuum oven at 60°C for 12 hours to obtain the intermediate product 1III; The usage ratio of the intermediate product 1II, carbon disulfide, tetrahydrofuran, deionized water B, chloroform, and anhydrous sodium sulfate is 0.1 mol: 0.2 mol: 100 mL: 60 mL: 100 mL: 10.0 g.
[0032] The amount of the catalyst B is 2.0-3.0wt% of the total mass of the reactants; The catalyst B may be lithium chloride, sodium iodide, lithium iodide, lithium bromide, etc.; and preferably lithium chloride.
[0033] S14, adding the intermediate product 1III and the diamine to dichloromethane A, stirring at room temperature for 0.5-2h, distilling under reduced pressure, eluting with anhydrous methanol A, and drying under vacuum at 50°C to constant weight to obtain the target product, i.e., polycarbonate-type polythiourethane.
[0034] The usage ratio of the intermediate product 1III, diamine, dichloromethane A, and anhydrous methanol A is 0.1 mol: 0.1 mol: 200 mL: 500 mL; The diamine is a macromolecular diamine and a small molecular diamine added in a molar ratio of 2.5-3.5:6.5-7.5.
[0035] The macromolecular diamine is polyethylene glycol diamine and / or polyether diamine; The molecular weight of the polyethylene glycol diamine is 300-1000, specifically 300, 400, 600, 1000, etc., or can be customized as required.
[0036] The molecular weight of the polyether diamine is 300-1000, specifically 300, 500, 600, 1000, etc., or can be customized as required.
[0037] The small molecule diamine is a mixture of aliphatic diamine and aromatic diamine in a molar ratio of 0.5-0.7:0.3-0.5.
[0038] The aliphatic diamine may be isophoronediamine, triethylenetetramine, tetraethylenepentamine, cyclohexanediamine, ethylenediamine, propylenediamine, tetramethylenediamine, pentanediamine, hexanediamine, 1,12-diaminododecane, etc., and triethylenetetramine is preferred.
[0039] The aromatic diamine may be p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, etc., and p-phenylenediamine is preferred.
[0040] The schematic formula for synthesizing polycarbonate-type polythiourethane S13 and S14 in the present invention is: S13: ; S14: The polycarbonate-type polythiourethane material described in the present invention is used as a matrix, which contains polycarbonate, polyurethane, and polysulfide rubber structures at the same time, and has excellent mechanical properties such as toughness, elasticity, and stretching; at the same time, the sulfur element (thiol) can improve the biocompatibility of the material; in addition, after molecular design, it also has a certain hydrophilicity; after a click cross-linking reaction with the carbon-carbon double bond, it can have the ability to resist complex forces as a whole.
[0041] The present invention also provides a method for preparing a polyamide-based fiber fabric, comprising the following steps: S21, add dibasic acid, polyamine and deionized water C into the reactor, protect with N2, heat to 240-260℃, 1.5-1.7MPa, react for 2-4h; reduce to normal pressure, continue to react for 2-3h; after the reaction is completed, evacuate for 1h to obtain the intermediate product 2I.
[0042] The usage ratio of the dibasic acid, polyamine and deionized water C is 0.5-1.0 mol: 1.0 mol: 300 mL; The dibasic acid is an aromatic diacid; The aromatic diacid may be terephthalic acid, 1,4-naphthalene dicarboxylic acid, 2,5-dimethyl-1,4-benzenedicarboxylic acid, 2,6-dimethyl-1,4-benzenedicarboxylic acid, 2-methyl-1,4-benzenedicarboxylic acid, 9,10-anthracene dicarboxylic acid, etc., and terephthalic acid is preferred.
[0043] The polyamine is a diamine and a triamine added in a molar ratio of 0.8-1.0:0-0.2; The diamine is a water-soluble diamine; including polyether diamine; The molecular weight of the polyether diamine is 300-1000, specifically 300, 500, 600, 1000, etc., or can be customized as required.
[0044] The triamine includes melamine; it can also be a mixture with 1,2,3-propylenetriamine or benzenetriamine.
[0045] S22, add intermediate product 1I and intermediate product 2I to dichloromethane B, stir at room temperature for 1.0-3.0 h, distill under reduced pressure, rinse with anhydrous methanol B, and dry under vacuum at 50° C. to constant weight to obtain intermediate product 2II.
[0046] The usage ratio of the intermediate product 1I, the intermediate product 2I, dichloromethane B, and anhydrous methanol B is 0.1 mol: 0.1 mol: 200 mL: 500 mL.
[0047] S23, dissolving the intermediate product 2II in deionized water D, stirring for 2-3 hours, degassing, passing through a spinning device under stirring conditions, combing with a carding machine, preparing by a needle punching method, and cutting, inspecting, and sterilizing to obtain a polyamide-based fiber fabric.
[0048] The usage ratio of the intermediate product 2II and deionized water D is 10 g:1000 mL.
[0049] The polyamide-based fiber fabric described in the present invention is used as an external material and is a block structure of polyamide and polythiourethane. First, the polyamide in the polyamide / polythiourethane structure has excellent mechanical strength, and polythiourethane has excellent compatibility with the matrix; at the same time, the dimensional stability of polyamide is combined with the flexibility of polythiourethane, and the advantages are complementary, so that the mechanical strength and dimensional stability of polyamide and the flexibility of polythiourethane can be combined; on the other hand, the thiol group in the polythiourethane structure can click-react with zwitterions to fix the position and avoid relative slippage under force, thereby affecting the support and shock absorption of the meniscus substitute. In addition, the amine sources in polyamide / polythiourethane are all water-soluble diamine structures, which can effectively improve the hydrophilic properties, provide lubrication effects, and reduce the friction coefficient.
[0050] The embodiment of the present invention also provides a method for preparing a polycarbonate-type polythiourethane meniscus substitute, comprising: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; The preparation methods of the molds described in the following embodiments of the present invention are: S311, acquiring image data of the recipient's knee joint, and processing the image data to obtain a three-dimensional model of the artificial meniscus; S312, optimizing the surface smoothness of the three-dimensional model of the artificial meniscus, converting the optimized three-dimensional model of the artificial meniscus into a three-dimensional model of a mold, and obtaining the mold by 3D printing.
[0051] The acquisition and processing of the image data refers to the acquisition through CT and nuclear magnetic resonance, and the processing of the acquired knee joint image data through medical reverse software to obtain a three-dimensional model of the artificial meniscus; the surface smoothness of the three-dimensional model is optimized, and the optimized three-dimensional model is converted into a three-dimensional model of the corresponding mold in the engineering software, and the mold is printed using a 3D printing device. That is, the artificial meniscus is prepared by combining 3D printing technology and molding technology, which can realize the personalized customization of the artificial meniscus to meet the replacement needs of different implant recipients.
[0052] The material of the mold can be stainless steel, aluminum, iron, polytetrafluoroethylene or ABS resin, etc. And the mold in the embodiment of the present invention is set as a stainless steel metal material piece.
[0053] S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; The polycarbonate-type polythiourethane solution described in the following examples of the present invention is prepared by mixing polycarbonate-type polythiourethane with N,N-dimethylformamide in a dosage ratio of 10 g:100 mL.
[0054] S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it at 40-50° C., and UV curing it for 5-30 minutes to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
[0055] The preparation method of the zwitterionic salt solution is as follows: In a dark environment, add zwitterion and bromide salt to the mixed solvent, stir for 0.5-1.0 h, add photoinitiator and continue stirring for 0.5 h to obtain a zwitterion salt solution.
[0056] The zwitterion and bromide salt are added in a molar ratio of 1:1 between the charge number of the positive ion and the bromide ion; The dosage ratio of the zwitterion and the mixed solvent is 1g:10g; The zwitterion contains a carbon-carbon double bond structure; it may be an allyl structure and / or an acryloxy structure; The positive ion of the zwitterion may be an ammonium ion or the like; The negative ions of the zwitterions may be phosphate ions, sulfonate ions, and the like.
[0057] The bromide salt may be potassium bromide, sodium bromide, calcium bromide, magnesium bromide, etc.; and potassium bromide is preferred.
[0058] The mixed solvent is deionized water and N,N-dimethylformamide mixed in a mass ratio of 1:2.
[0059] The amount of the photoinitiator is 0-2.0wt% of the mass of the zwitterionic salt; The photoinitiator is a commonly used photoinitiator, which may be photoinitiator 1173, photoinitiator 184, photoinitiator 2959, photoinitiator 369 or photoinitiator TPO, etc.; and the photoinitiator described in the following embodiments of the present invention is photoinitiator 1173.
[0060] The UV light intensity is 200-600 mW / cm 2 ; Specifically, it can be 200mW / cm 2 、300 mW / cm 2 , 400 mW / cm 2 , 500 mW / cm 2 , 600 mW / cm 2 ; and, the UV light intensity described in the following embodiments of the present invention is 400 mW / cm 2 .
[0061] The polycarbonate-type polythiourethane meniscus substitute of the present invention uses self-made polycarbonate-type polythiourethane as a matrix material and a polyamide-based fiber fabric as an external "binding" material. After being impregnated with zwitterions, the thiol groups in the matrix material and the thiol groups in the polythiourethane structure of the external "binding" material can both undergo a "thiol-ene" click reaction, so that the external "binding" material reacts nearby and firmly wraps the matrix material to form an integrated material; at the same time, the bromide ions in the zwitterions react with the ammonium ions and phosphate ions (or sulfonate ions) in the zwitterion salt due to electrostatic force and ring tension, and the ion radius of the bromide ions is smaller than that of the atomic clusters of the ammonium ions and phosphate ions (or sulfonate ions), so that the bromide ions are more easily combined with the positive and negative ions of the ammonium ions, thereby improving the sustained release effect of the bromide ions, promoting the proliferation and differentiation of chondrocytes, compensating for the worn cartilage, and improving the service life.
[0062] In order to further understand the present invention, a polycarbonate-type polythiourethane meniscus substitute provided by the present invention is described in detail below in conjunction with specific embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0063] A method for preparing a polycarbonate-type polythiourethane comprises the following steps: S11, N2 protection, 1,4-butanediol and dimethyl carbonate were mixed, tetrabutyl titanate was added, stirred, heated to 170°C, reacted for 1.5h, and the intermediate product 1I was obtained.
[0064] The molar ratio of 1,4-butanediol to dimethyl carbonate is 2.0:1.
[0065] The amount of tetrabutyl titanate used is 0.1wt% of the total mass of the reactants.
[0066] Its infrared data are as follows: 3418 cm -1 :-OH exists and weakens; 1732cm -1 :-C=O exists.
[0067] Its NMR data are as follows ( 1 H NMR, CDCl3 as solvent, TMS as internal standard, δ ppm): 4.20 (-CH2-, 4H); 3.72 (-CH2-, 4H); 1.85 (-CH2-, 4H); 1.22 (-OH, 2H).
[0068] S12, the intermediate product 1I, epichlorohydrin and BF3 ether are mixed, heated to 60°C, and reacted for 6 hours; allowed to stand, and distilled under reduced pressure at 40°C to obtain a concentrate; sodium hydroxide solution is added, stirred at 60°C for 3 hours, and concentrated by distillation under reduced pressure, and washed with deionized water A three times to obtain the intermediate product 1II; The usage ratio of the intermediate product 1I, epichlorohydrin, sodium hydroxide, and deionized water A is 1 mol: 2 mol: 2 mol: 500 mL; The amount of BF3 ether used is 2.5wt% of the total mass of the reactants; The concentration of the sodium hydroxide solution is 30wt%.
[0069] Its infrared data are as follows: 3418 cm -1 :-OH does not exist; 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm -1 : Epoxy groups exist; 747cm -1 :-C-Cl does not exist.
[0070] S13, add the intermediate product 1II, carbon disulfide and lithium chloride to tetrahydrofuran, place in an ice bath, stir for 3 hours, remove the ice bath, and continue stirring at room temperature for 20 hours; after the reaction is completed, distill under reduced pressure, add deionized water B, and shake; add chloroform to extract, separate the liquids, take the oil phase, add anhydrous sodium sulfate to dry, filter, take the filtrate, distill under reduced pressure, and dry in a vacuum oven at 60°C for 12 hours to obtain the intermediate product 1III; The usage ratio of the intermediate product 1II, carbon disulfide, tetrahydrofuran, deionized water B, chloroform, and anhydrous sodium sulfate is 0.1 mol: 0.2 mol: 100 mL: 60 mL: 100 mL: 10.0 g.
[0071] The amount of lithium chloride used is 2.5wt% of the total mass of the reactants.
[0072] Its infrared data are as follows: 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm -1 : Epoxy group does not exist; 1066cm -1 :-C=S exists; 701 cm -1 :-CS exists.
[0073] S14, the intermediate product 1III and the diamine are added to dichloromethane A, stirred at room temperature for 1.0 h, distilled under reduced pressure, rinsed with anhydrous methanol A, and dried under vacuum at 50° C. to constant weight to obtain the target product, i.e., polycarbonate-type polythiourethane.
[0074] The usage ratio of the intermediate product 1III, diamine, dichloromethane A, and anhydrous methanol A is 0.1 mol: 0.1 mol: 200 mL: 500 mL; The diamines are macromolecular diamine and micromolecular diamine, which are added in a molar ratio of 3.0:7.0.
[0075] The macromolecular diamine is polyethylene glycol diamine 400; The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0.6:0.4.
[0076] Its infrared data are as follows: 3320 cm -1 :-NH- exists; 2550 cm -1 :-SH exists; 1732cm -1 :-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0077] A method for preparing a polyamide-based fiber fabric comprises the following steps: S21, add terephthalic acid, polyamine and deionized water C into the reactor, protect with N2, heat to 250°C, 1.6MPa, react for 3h; reduce to normal pressure, continue to react for 2.5h; after the reaction is completed, evacuate for 1h to obtain the intermediate product 2I.
[0078] The usage ratio of terephthalic acid, polyamine and deionized water C is 0.8 mol:1.0 mol:300 mL.
[0079] The polyamine is a diamine and a triamine added in a molar ratio of 0.9:0.1; The diamine is polyether diamine 500; The teramine is a mixture of melamine and 1,2,3-propylenetriamine in a molar ratio of 0.6:0.4.
[0080] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 1664cm -1 :Amide-C=O exists; 3402cm -1 :-OH does not exist; 1764cm -1 : Carboxylic acid -C=O does not exist.
[0081] S22, add intermediate product 1I and intermediate product 2I to dichloromethane B, stir at room temperature for 2.0 h, distill under reduced pressure, rinse with anhydrous methanol B, and dry under vacuum at 50° C. to constant weight to obtain intermediate product 2II.
[0082] The usage ratio of the intermediate product 1I, the intermediate product 2I, dichloromethane B, and anhydrous methanol B is 0.1 mol: 0.1 mol: 200 mL: 500 mL.
[0083] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 : Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0084] S23, dissolving the intermediate product 2II in deionized water D, stirring for 2.5 hours, degassing, passing through a spinning device under stirring conditions, combing with a carding machine, preparing by a needle punching method, and cutting, inspecting, and sterilizing to obtain a polyamide-based fiber fabric.
[0085] The usage ratio of the intermediate product 2II and deionized water D is 10 g:1000 mL.
[0086] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1:-C=S exists; 718 cm -1 :-CS exists.
[0087] A method for preparing a polycarbonate-type polythiourethane meniscus substitute comprises: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; The polycarbonate-type polythiourethane solution described in the following examples of the present invention is prepared by mixing polycarbonate-type polythiourethane with N,N-dimethylformamide in a dosage ratio of 10 g:100 mL.
[0088] S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it at 50° C., and UV curing it for 10 minutes to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
[0089] The preparation method of the zwitterionic salt solution is as follows: In a dark environment, add zwitterion and potassium bromide to the mixed solvent, stir for 1.0 h, add photoinitiator and continue stirring for 0.5 h to obtain a zwitterion salt solution.
[0090] The zwitterion and potassium bromide are added in a molar ratio of 1:1 between the charge number of the positive ion and the bromide ion; The dosage ratio of the zwitterion and the mixed solvent is 1g:10g; The zwitterion is 2-methacryloyloxyethyl phosphorylcholine and soybean lecithin added in a molar ratio of 0.8:0.2.
[0091] The mixed solvent is deionized water and N,N-dimethylformamide mixed in a mass ratio of 1:2.
[0092] The amount of the photoinitiator used is 1.0 wt % of the mass of the zwitterionic salt.
[0093] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH does not exist; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1:-C=S exists; 718 cm -1 :-CS exists; 1187cm -1 :-P=O exists; 1621cm -1 、1606cm -1 、811cm -1 :-C=C- does not exist.
[0094] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane comprises the following steps: S11, N2 protection, 1,4-butanediol and dimethyl carbonate were mixed, tetrabutyl titanate was added, stirred, heated to 160°C, and reacted for 3h to obtain the intermediate product 1I.
[0095] The molar ratio of 1,4-butanediol to dimethyl carbonate is 2.0:1.
[0096] The amount of tetrabutyl titanate used is 0.2 wt % of the total mass of the reactants.
[0097] Its infrared data are as follows: 3418 cm -1 :-OH exists and weakens; 1732cm -1 :-C=O exists.
[0098] Its NMR data are as follows ( 1 H NMR, CDCl3 as solvent, TMS as internal standard, δ ppm): 4.20 (-CH2-, 4H); 3.72 (-CH2-, 4H); 1.85 (-CH2-, 4H); 1.22 (-OH, 2H).
[0099] S12, the intermediate product 1I, epichlorohydrin and BF3 ether are mixed, heated to 40°C, and reacted for 8 hours; allowed to stand, and distilled under reduced pressure at 40°C to obtain a concentrate; sodium hydroxide solution is added, stirred at 40°C for 5 hours, and concentrated by distillation under reduced pressure, and washed with deionized water A three times to obtain the intermediate product 1II; The usage ratio of the intermediate product 1I, epichlorohydrin, sodium hydroxide, and deionized water A is 1 mol: 2 mol: 2 mol: 500 mL; The amount of BF3 ether used is 3.0wt% of the total mass of the reactants; The concentration of the sodium hydroxide solution is 30wt%.
[0100] Its infrared data are as follows: 3418 cm -1 :-OH does not exist; 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm-1 : Epoxy groups exist; 747cm -1 :-C-Cl does not exist.
[0101] S13, add the intermediate product 1II, carbon disulfide and lithium chloride to tetrahydrofuran, place in an ice bath, stir for 4 hours, remove the ice bath, and continue stirring at room temperature for 18 hours; after the reaction is completed, distill under reduced pressure, add deionized water B, and shake; add chloroform to extract, separate the liquids, take the oil phase, add anhydrous sodium sulfate to dry, filter, take the filtrate, distill under reduced pressure, and dry in a vacuum oven at 60°C for 12 hours to obtain the intermediate product 1III; The usage ratio of the intermediate product 1II, carbon disulfide, tetrahydrofuran, deionized water B, chloroform, and anhydrous sodium sulfate is 0.1 mol: 0.2 mol: 100 mL: 60 mL: 100 mL: 10.0 g.
[0102] The amount of lithium chloride used is 2.0wt% of the total mass of the reactants.
[0103] Its infrared data are as follows: 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm -1 : Epoxy group does not exist; 1066cm -1 :-C=S exists; 701 cm -1 :-CS exists.
[0104] S14, adding the intermediate product 1III and the diamine to dichloromethane A, stirring at room temperature for 0.5 h, distilling under reduced pressure, eluting with anhydrous methanol A, and drying under vacuum at 50° C. to constant weight to obtain the target product, i.e., polycarbonate-type polythiourethane.
[0105] The usage ratio of the intermediate product 1III, diamine, dichloromethane A, and anhydrous methanol A is 0.1 mol: 0.1 mol: 200 mL: 500 mL; The diamines are macromolecular diamine and micromolecular diamine, which are added in a molar ratio of 3.0:7.0.
[0106] The macromolecular diamine is polyethylene glycol diamine 400; The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0.6:0.4.
[0107] Its infrared data are as follows: 3320 cm -1 :-NH- exists; 2550 cm -1 :-SH exists; 1732cm -1 :-C=O exists; 1078cm -1:-C=S exists; 718 cm -1 :-CS exists.
[0108] A method for preparing a polyamide-based fiber fabric comprises the following steps: S21, add terephthalic acid, polyamine and deionized water C into the reactor, protect with N2, heat to 240°C, 1.7MPa, react for 4h; reduce to normal pressure, continue to react for 3h; after the reaction is completed, evacuate for 1h to obtain the intermediate product 2I.
[0109] The usage ratio of terephthalic acid, polyamine and deionized water C is 0.8 mol:1.0 mol:300 mL.
[0110] The polyamine is a diamine and a triamine added in a molar ratio of 0.9:0.1; The diamine is polyether diamine 500; The teramine is a mixture of melamine and 1,2,3-propylenetriamine in a molar ratio of 0.6:0.4.
[0111] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 1664cm -1 :Amide-C=O exists; 3402cm -1 :-OH does not exist; 1764cm -1 : Carboxylic acid -C=O does not exist.
[0112] S22, add intermediate product 1I and intermediate product 2I to dichloromethane B, stir at room temperature for 1.0 h, distill under reduced pressure, rinse with anhydrous methanol B, and dry under vacuum at 50° C. to constant weight to obtain intermediate product 2II.
[0113] The usage ratio of the intermediate product 1I, the intermediate product 2I, dichloromethane B, and anhydrous methanol B is 0.1 mol: 0.1 mol: 200 mL: 500 mL.
[0114] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0115] S23, dissolving the intermediate product 2II in deionized water D, stirring for 2 hours, degassing, passing through a spinning device under stirring conditions, combing with a carding machine, preparing by a needle punching method, and cutting, inspecting, and sterilizing to obtain a polyamide-based fiber fabric.
[0116] The usage ratio of the intermediate product 2II and deionized water D is 10 g:1000 mL.
[0117] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0118] A method for preparing a polycarbonate-type polythiourethane meniscus substitute comprises: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; The polycarbonate-type polythiourethane solution described in the following examples of the present invention is prepared by mixing polycarbonate-type polythiourethane with N,N-dimethylformamide in a dosage ratio of 10 g:100 mL.
[0119] S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it at 45° C., and UV curing it for 5 minutes to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
[0120] The preparation method of the zwitterionic salt solution is as follows: In a dark environment, add zwitterion and potassium bromide to the mixed solvent, stir for 0.5 h, add photoinitiator and continue stirring for 0.5 h to obtain a zwitterion salt solution.
[0121] The zwitterion and potassium bromide are added in a molar ratio of 1:1 between the charge number of the positive ion and the bromide ion; The dosage ratio of the zwitterion and the mixed solvent is 1g:10g; The zwitterion is 2-methacryloyloxyethyl phosphorylcholine and soybean lecithin added in a molar ratio of 0.8:0.2.
[0122] The mixed solvent is deionized water and N,N-dimethylformamide mixed in a mass ratio of 1:2.
[0123] The amount of the photoinitiator used is 2.0 wt % of the mass of the zwitterionic salt.
[0124] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH does not exist; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists; 1187cm -1 :-P=O exists; 1621cm -1 、1606cm -1 、811cm -1 :-C=C- does not exist.
[0125] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane comprises the following steps: S11, N2 protection, 1,4-butanediol and dimethyl carbonate were mixed, tetrabutyl titanate was added, stirred, heated to 180°C, reacted for 1h, and the intermediate product 1I was obtained.
[0126] The molar ratio of 1,4-butanediol to dimethyl carbonate is 2.0:1.
[0127] The amount of tetrabutyl titanate used is 0.05wt% of the total mass of the reactants.
[0128] Its infrared data are as follows: 3418 cm -1 :-OH exists and weakens; 1732cm -1 :-C=O exists.
[0129] Its NMR data are as follows ( 1 H NMR, CDCl3 as solvent, TMS as internal standard, δ ppm): 4.20 (-CH2-, 4H); 3.72 (-CH2-, 4H); 1.85 (-CH2-, 4H); 1.22 (-OH, 2H).
[0130] S12, the intermediate product 1I, epichlorohydrin and BF3 ether are mixed, heated to 80°C, and reacted for 2 hours; allowed to stand, and distilled under reduced pressure at 40°C to obtain a concentrate; sodium hydroxide solution is added, stirred at 80°C for 0.5 hours, and concentrated by distillation under reduced pressure, and washed with deionized water A three times to obtain the intermediate product 1II; The usage ratio of the intermediate product 1I, epichlorohydrin, sodium hydroxide, and deionized water A is 1 mol: 2 mol: 2 mol: 500 mL; The amount of BF3 ether used is 2.0wt% of the total mass of the reactants; The concentration of the sodium hydroxide solution is 30wt%.
[0131] Its infrared data are as follows: 3418 cm -1 :-OH does not exist; 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm -1 : Epoxy groups exist; 747cm -1 :-C-Cl does not exist.
[0132] S13, add the intermediate product 1II, carbon disulfide and lithium chloride to tetrahydrofuran, place in an ice bath, stir for 2 hours, remove the ice bath, and continue stirring at room temperature for 24 hours; after the reaction is completed, distill under reduced pressure, add deionized water B, and shake; add chloroform to extract, separate the liquids, take the oil phase, add anhydrous sodium sulfate to dry, filter, take the filtrate, distill under reduced pressure, and dry in a vacuum oven at 60°C for 12 hours to obtain the intermediate product 1III; The usage ratio of the intermediate product 1II, carbon disulfide, tetrahydrofuran, deionized water B, chloroform, and anhydrous sodium sulfate is 0.1 mol: 0.2 mol: 100 mL: 60 mL: 100 mL: 10.0 g.
[0133] The amount of lithium chloride used is 3.0wt% of the total mass of the reactants.
[0134] Its infrared data are as follows: 1732cm -1 :-C=O exists; 1269cm -1 、938cm -1 、825cm -1 : Epoxy group does not exist; 1066cm -1 :-C=S exists; 701 cm -1 :-CS exists.
[0135] S14, adding the intermediate product 1III and the diamine to dichloromethane A, stirring at room temperature for 2 h, distilling under reduced pressure, eluting with anhydrous methanol A, and drying under vacuum at 50° C. to constant weight to obtain the target product, i.e., polycarbonate-type polythiourethane.
[0136] The usage ratio of the intermediate product 1III, diamine, dichloromethane A, and anhydrous methanol A is 0.1 mol: 0.1 mol: 200 mL: 500 mL; The diamines are macromolecular diamine and micromolecular diamine, which are added in a molar ratio of 3.0:7.0.
[0137] The macromolecular diamine is polyethylene glycol diamine 400; The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0.6:0.4.
[0138] Its infrared data are as follows: 3320 cm -1 :-NH- exists; 2550 cm -1 :-SH exists; 1732cm -1 :-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0139] A method for preparing a polyamide-based fiber fabric comprises the following steps: S21, add terephthalic acid, polyamine and deionized water C into the reactor, protect with N2, heat to 260°C, 1.5MPa, react for 2h; reduce to normal pressure, continue to react for 2h; after the reaction is completed, evacuate for 1h to obtain the intermediate product 2I.
[0140] The usage ratio of terephthalic acid, polyamine and deionized water C is 0.8 mol:1.0 mol:300 mL.
[0141] The polyamine is a diamine and a triamine added in a molar ratio of 0.9:0.1; The diamine is polyether diamine 500; The teramine is a mixture of melamine and 1,2,3-propylenetriamine in a molar ratio of 0.6:0.4.
[0142] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 1664cm -1 :Amide-C=O exists; 3402cm -1 :-OH does not exist; 1764cm -1 : Carboxylic acid -C=O does not exist.
[0143] S22, add intermediate product 1I and intermediate product 2I to dichloromethane B, stir at room temperature for 3.0 h, distill under reduced pressure, rinse with anhydrous methanol B, and dry under vacuum at 50° C. to constant weight to obtain intermediate product 2II.
[0144] The usage ratio of the intermediate product 1I, the intermediate product 2I, dichloromethane B, and anhydrous methanol B is 0.1 mol: 0.1 mol: 200 mL: 500 mL.
[0145] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0146] S23, dissolving the intermediate product 2II in deionized water D, stirring for 3 hours, degassing, passing through a spinning device under stirring conditions, combing with a carding machine, preparing by a needle punching method, and cutting, inspecting, and sterilizing to obtain a polyamide-based fiber fabric.
[0147] The usage ratio of the intermediate product 2II and deionized water D is 10 g:1000 mL.
[0148] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH exists; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists.
[0149] A method for preparing a polycarbonate-type polythiourethane meniscus substitute comprises: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; The polycarbonate-type polythiourethane solution described in the following examples of the present invention is prepared by mixing polycarbonate-type polythiourethane with N,N-dimethylformamide in a dosage ratio of 10 g:100 mL.
[0150] S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it at 40° C., and UV curing it for 20 minutes to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
[0151] The preparation method of the zwitterionic salt solution is as follows: In a dark environment, add zwitterion and potassium bromide to the mixed solvent, stir for 1.0 h, add photoinitiator and continue stirring for 0.5 h to obtain a zwitterion salt solution.
[0152] The zwitterion and potassium bromide are added in a molar ratio of 1:1 between the charge number of the positive ion and the bromide ion; The dosage ratio of the zwitterion and the mixed solvent is 1g:10g; The zwitterion is 2-methacryloyloxyethyl phosphorylcholine and soybean lecithin added in a molar ratio of 0.8:0.2.
[0153] The mixed solvent is deionized water and N,N-dimethylformamide mixed in a mass ratio of 1:2.
[0154] The amount of the photoinitiator used is 0.5wt% of the mass of the zwitterionic salt.
[0155] Its infrared data are as follows: 3322 cm -1 :-NH- exists; 3017 cm -1 :-CH benzene ring exists; 2550 cm -1 :-SH does not exist; 1732cm -1 :Ester-C=O exists; 1664cm -1 :Amide-C=O exists; 1078cm -1 :-C=S exists; 718 cm -1 :-CS exists; 1187cm -1 :-P=O exists; 1621cm -1 、1606cm -1 、811cm -1 :-C=C- does not exist.
[0156] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S11, The molar ratio of 1,4-butanediol to dimethyl carbonate is 1.5:1.
[0157] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S11, The molar ratio of 1,4-butanediol to dimethyl carbonate is 2.5:1.
[0158] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The diamines are macromolecular diamine and small molecular diamine, which are added in a molar ratio of 2.5:7.5.
[0159] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The diamines are macromolecular diamine and micromolecular diamine, which are added in a molar ratio of 3.5:6.5.
[0160] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The macromolecular diamine is polyether diamine 500.
[0161] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0.5:0.5.
[0162] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0.7:0.3.
[0163] The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S21, The usage ratio of terephthalic acid, polyamine and deionized water C is 0.5 mol:1.0 mol:300 mL.
[0164] The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S21, The usage ratio of terephthalic acid, polyamine and deionized water C is 0.95 mol:1.0 mol:300 mL.
[0165] The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S21, The polyamine is a diamine and a triamine added in a molar ratio of 0.8:0.2.
[0166] The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S21, The polyamine is a diamine and a triamine added in a molar ratio of 1.0:0; that is, no triamine is added.
[0167] The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S21, The teramine is a mixture of melamine and 1,3,5-triaminobenzene in a molar ratio of 0.6:0.4.
[0168] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute, wherein in S34, The UV curing time is 30 minutes; The amount of the photoinitiator used is 0wt% of the mass of the zwitterionic salt; that is, no photoinitiator is added.
[0169] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute, wherein in S34, The zwitterion is 2-methacryloyloxyethyl phosphorylcholine.
[0170] The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute, wherein in S34, The zwitterion is methacryloylethyl sulfobetaine.
[0171] A polycarbonate type polythiourethane meniscus substitute in the following comparative examples is compared with Example 1: Comparative Example 1 The rest is the same as in Example 1, except that: A method for preparing polycarbonate type polythiourethane, The intermediate III was replaced with neopentyl glycol diglycidyl ether.
[0172] Comparative Example 2 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The diamine is a macromolecular diamine and a small molecular diamine added in a molar ratio of 0:10, that is, no macromolecular diamine is added.
[0173] Comparative Example 3 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 0:1.0; that is, no triethylenetetramine is added.
[0174] Comparative Example 4 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane, wherein in S14, The small molecule diamine is a mixture of triethylenetetramine and p-phenylenediamine in a molar ratio of 1.0:0; that is, p-phenylenediamine is not added.
[0175] Comparative Example 5 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute does not include step S32, that is, no polyamide-based fiber fabric is provided on the outer layer.
[0176] Comparative Example 6 The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric. In S21, the usage ratio of terephthalic acid, polyamine and deionized water C is 1.0 mol:1.0 mol:300 mL.
[0177] In S23, the intermediate 2II is replaced by 2I.
[0178] Comparative Example 7 The rest is the same as in Example 1, except that: A method for preparing a polyamide-based fiber fabric, wherein in S23, The intermediate product 2II is replaced with polycarbonate-type polythiourethane.
[0179] Comparative Example 8 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute does not include step S34; that is, the S34 operation is not performed.
[0180] Comparative Example 9 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute, wherein in S34, The dosage ratio of the zwitterion and potassium bromide is 1:0 according to the molar ratio of the charge number of the positive ion to the bromide ion; that is, potassium bromide is not added.
[0181] Comparative Example 10 The rest is the same as in Example 1, except that: A method for preparing a polycarbonate-type polythiourethane meniscus substitute, wherein in S34, The zwitterion and potassium bromide are added at a molar ratio of the charge number of the positive ion to the bromide ion of 0:1; that is, no zwitterion is added; and The usage ratio of potassium bromide and mixed solvent is 1g:10g.
[0182] The physical properties of the polycarbonate-type polythiourethane meniscus substitutes prepared in Examples 1-18 of the present invention and Comparative Examples 1-10 were measured respectively, and the results are shown in Table 1.
[0183] First, it can be concluded from Examples 1-18 in Table 1 that the polycarbonate-type polythiourethane meniscus substitute of the present invention has excellent mechanical properties, low friction properties, biocompatibility, and the ability to promote chondrocyte proliferation and differentiation.
[0184] Second, it can be observed from Example 1 and Comparative Examples 1-4 that the polycarbonate-type polythiourethane meniscus substitute of the present invention uses self-made polycarbonate-type polythiourethane as the internal matrix material, which can effectively improve the mechanical properties. Among them, it can be observed from Comparative Example 1 that the carbonate structure can effectively improve the mechanical properties; it can be observed from Comparative Example 2 that the macromolecular diamine structure is a water-soluble structure, which can effectively improve the toughness and lubricity, which is reflected in the reduction of the friction coefficient; it can be observed from Examples 3-4 that the ratio of different aliphatic diamines to aromatic diamines has a certain influence on the mechanical properties.
[0185] Third, it can be observed from Example 1 and Comparative Examples 5-7 that the polycarbonate-type polythiourethane meniscus substitute of the present invention uses a homemade polyamide-based fiber fabric as an external material, which has the characteristics of improving mechanical properties and reducing friction coefficient.
[0186] Fourth, it can be observed from Example 1 and Comparative Examples 8-10 that the zwitterions in the zwitterionic salt solution have excellent hydrophilic lubrication and friction reduction effects; and the bromide ions have the effect of promoting chondrocyte proliferation, which plays a role in promoting cartilage repair, can compensate for the wear of cartilage tissue, and extend the service life of the material; in addition, the zwitterions act as cross-linking agents to reduce the relative slip between the matrix and the external material and improve the mechanical properties.
[0187] In summary, the polycarbonate-type polythiourethane meniscus substitute of the present invention uses a homemade polycarbonate-type polythiourethane material as an internal matrix material and a homemade polyamide-based fiber fabric as an external restraining material, and is prepared by impregnation with a zwitterionic salt solution and UV curing reaction, and has obvious advantages in mechanical properties, low wear, and promotion of chondrocyte proliferation.
[0188] The test method is as follows: (1) Elastic modulus, tensile strength, and elongation at break: Tested in accordance with the method described in GB / T 1040.3-2006. The samples to be tested were immersed in sterile phosphate buffer at 37°C for 0, 48, and 96 days, and then taken out and stabilized to room temperature for testing.
[0189] (2) Friction coefficient: The friction tester (BRUKER UMT) was used for testing. The test conditions were reciprocating motion, 1 Hz frequency, 0.4 N load, simulated joint fluid lubrication, porcine femoral condylar cartilage as the friction pair, and room temperature. The test was terminated when the friction coefficient was constant. The samples were immersed in sterile phosphate buffer at 37°C for 0, 48, and 96 days, and then taken out and stabilized to room temperature for testing.
[0190] (3) Cytotoxicity: Referring to the standard GB / T 16886.5-2003, the material was immersed in the culture medium for 7 and 14 days, and the extract was used to culture NIH3T3 cells, and then the cytotoxicity was evaluated (relative cell survival rate>80%, which means good biocompatibility).
[0191] (4) Cell differentiation test: On the 14th day of ATDC5 cell culture, the content of glycosaminoglycan (GAG) secreted by the cultured ATDC5 cells differentiated into chondrocytes was quantitatively detected, and the dsDNA (double-stranded DNA) content was measured. The content of dsDNA per microgram was calculated, and then the data was normalized.
[0192] Preparation of papain lysis buffer: Dissolve the following ingredients in PBS: 50 mM Na3PO4, 20 mM Nacetyl cysteine, 28 μL / mL papain, filter through 0.22 μm filter membrane, and store at 4°C.
[0193] Lysis of cells: Transfer the cultured monolayer cells or cultured cell clusters to the well plate, wash twice with PBS, add 300 μL papain lysis solution to the well plate, seal the well plate with sealing film and keep it in a 60℃ water bath for 16 hours. After completion, centrifuge the well plate and mix the lysis solution by blowing with a 200μL pipette tip. Transfer the lysis solution to a 1.5mL EP tube, centrifuge and take the supernatant for immediate determination or store at 80℃ for later use. This sample is used for the determination of double-stranded DNA (ds DNA) and GAG content.
[0194] Determination of ds DNA content: The lysate samples obtained by cell lysis were taken and the concentration of dsDNA was tested by Nanodrop instrument.
[0195] GAG content determination: The lysate sample obtained by cell lysis was reacted with DMMB staining solution at a volume ratio of 1:6. After completion, the absorbance at 525 nm was detected on an ELISA reader and standardized with the ds DNA content to calculate the relative content of GAG per microgram of ds DNA.
[0196] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a polycarbonate-type polythiourethane, characterized in that: The following steps are involved: S11, conducting an ester exchange reaction between a diol and dimethyl carbonate to obtain an intermediate product 1I; S12, subjecting the intermediate product 1I to a ring-opening-cyclization reaction with epichlorohydrin to obtain an intermediate product 1II; S13, subjecting the intermediate product 1II to a ring-opening-cyclization reaction with carbon disulfide to obtain an intermediate product 1III; and S14, subjecting the intermediate product 1III to a ring-opening reaction with a diamine to obtain a target product, namely, a polycarbonate-type polythiourethane.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the diol to dimethyl carbonate is 1.5-2.5:
1.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the intermediate product 1I to epichlorohydrin is 1:
2.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the intermediate product III to carbon disulfide is 1:
2.
5. The preparation method according to claim 1, characterized in that: The molar ratio of the intermediate product 1III to the diamine is 1:1; and The diamine is a macromolecular diamine and a small molecular diamine added in a molar ratio of 2.5-3.5:6.5-7.
5.
6. The preparation method according to claim 5, characterized in that: The macromolecular diamine is polyethylene glycol diamine and / or polyether diamine; and The small molecule diamine is a mixture of aliphatic diamine and aromatic diamine.
7. A polycarbonate-type polythiourethane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. A method for preparing a polyamide-based fiber fabric, characterized in that: The following steps are involved: S21, condensing a dibasic acid and a polyamine to obtain an intermediate product 2I; S22, subjecting the intermediate product 1I to a ring-opening reaction with the intermediate product 2I to obtain the intermediate product 2II; S23, spinning and combing the intermediate product 2II to obtain a polyamide-based fiber fabric.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the dibasic acid to the polyamine is 0.5-1.0:1.0; and The dibasic acid is an aromatic dibasic acid; The polyamine is a diamine and a triamine added in a molar ratio of 0.80-0.95:0.05-0.20; The diamine is a water-soluble diamine; including polyether diamines; The triamine includes melamine.
10. The preparation method according to claim 8, characterized in that: The intermediate product 2I and the intermediate product 2II are added in a molar ratio of 1.0:1.
0.
11. A polyamide-based fiber fabric, characterized in that: Prepared by the preparation method according to any one of claims 8 to 10.
12. A method for preparing a polycarbonate-type polythiourethane meniscus substitute, characterized in that: include: S31, preparing a mold for making a disc-shaped polycarbonate-based polythiourethane meniscus substitute; S32, arranging a polyamide-based fiber fabric inside the mold; S33, adding a polycarbonate type polythiourethane solution into the mold, removing bubbles, and allowing to stand to obtain a molded object I; wherein the outer end of the polycarbonate-type polythiourethane meniscus substitute is connected to the polyamide-based fiber fabric; S34, immersing the formed article I in a zwitterionic salt solution, taking it out, drying it, and curing it to obtain the target product, i.e., a polycarbonate-type polythiourethane meniscus substitute.
13. The preparation method according to claim 12, characterized in that: The zwitterionic salt contains a carbon-carbon double bond structure; and The zwitterionic salt contains bromide ions.
14. A polycarbonate-type polythiourethane meniscus substitute, characterized in that: Prepared by the preparation method according to any one of claims 12-13.